Using MSK Ultrasound in the Evaluation of Subscapularis Injuries - Robert C. Manske; Michael Voight; Chris Wolfe; Phil Page (North American Sports Medicine Institute, 2023)
The shoulder is an area that can be prone to a variety of injuries, including subscapularis tendon tears. The subscapularis muscle is one of the four muscles that make up the rotator cuff in the shoulder and plays an essential role in stabilizing the shoulder joint while at the same time facilitating internal rotation of the humerus. Injuries to the subscapularis can occur due to trauma, overuse, or degeneration, leading to pain, weakness, and limited mobility. When injury occurs, subscapularis tendon tears are often difficult to diagnose and evaluate due to their location deep within the shoulder joint. While traditional imaging techniques like radiographs, and magnetic resonance imaging may give us insight into the structures present, they do not always provide detailed enough information for clinicians. Ultrasound has become increasingly popular in musculoskeletal (MSK) rehabilitation as it allows for direct visualization of soft tissue abnormalities like tendinopathies or subtle rotator cuff tear patterns. In this Ultrasound Bites article, we will discuss how MSK ultrasound can be used in the evaluation of subscapularis tendon pathology with a specific focus on its utility in the physical therapy clinic.